Halogen-free flame-retardant TPU material and preparation method thereof
By using vinyl modified aluminum nitride and furanite nanotubes in TPU materials to construct a hybrid three-dimensional network, and combining flexible carboxylated cellulose nanofibers to form a multi-stage dense carbon layer, the problem of poor flame retardant performance of TPU materials is solved and a more efficient flame retardant effect is achieved.
Patent Information
- Application Number
- CN202411951902.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-25
AI Technical Summary
TPU materials have poor flame retardant properties, are prone to combustion and release a large amount of smoke, resulting in fire and safety hazards.
A hybrid three-dimensional network is constructed by combining vinyl modified aluminum nitride and furan-group grafted elosite nanotubes, and a thermal conductivity network is formed through reversible Diels-Alder reaction, and a multi-stage dense carbon layer is formed by combining flexible carboxylated cellulose nanofibers, aluminum nitride and elosite nanotubes to form a multi-stage dense carbon layer to enhance flame retardant performance.
Take away heat in the early stage of combustion to extend the ignition time, break the thermal conduction path during combustion, prevent heat transfer, reduce the release of smoke and combustible gases, and significantly improve the flame retardant performance of TPU materials.
Smart Images

Figure BDA0005215058420000081 
Figure BDA0005215058420000101
Abstract
Description
Technical Field
[0001] The invention relates to the field of functional plastics, and in particular to a halogen-free flame-retardant TPU material and a preparation method thereof. Background Art
[0002] Since the 21st century, with the acceleration of modernization and urbanization, the use of polymer materials has covered all aspects of life, work and production. As an engineering thermoplastic with excellent performance, thermoplastic polyurethane elastomer (TPU) is widely used in the production of films, pipes, wires and cables and other products; however, like most polymer materials, TPU is easy to burn when exposed to fire, and it produces a large amount of smoke, which will cause direct casualties and property losses when a fire occurs. At present, in order to reduce the huge harm caused by fire caused by polymer materials such as TPU, people pay more and more attention to the performance of flame retardant properties when selecting and using polymer materials. Adding flame retardants to polymer matrices is a common method for flame retardant polymer materials. Flame retardants are chemical additives that improve the flame retardancy of polymer materials. They can prevent polymer materials from being ignited and delay the spread of flames. Flame retardants are divided into two categories according to the method of use: additive flame retardants and reactive flame retardants. Reactive flame retardants refer to a class of compounds that participate in the reaction in the polymer polymerization process in the form of monomers, and are currently less used. Additive flame retardants have a wider range of uses. According to the elements that play a role, they can be divided into: nitrogen flame retardants, silicon flame retardants, halogen flame retardants, phosphorus flame retardants, boron flame retardants, intumescent flame retardants and inorganic hydroxide flame retardants, etc.; they also include some synergists and smoke suppressants, such as molybdenum oxide, tin oxide, zinc oxide, ammonium octamolybdate, ammonium decamolybdate and antimony trioxide, etc. Based on the disadvantages of traditional flame retardants such as halogen flame retardants, large smoke production, and the released hydrogen halide gas has strong corrosiveness and toxicity. Therefore, the development of environmentally friendly halogen-free flame-retardant TPU materials has become a research hotspot for flame-retardant materials. Summary of the invention
[0003] Technical problem to be solved: In order to solve the technical problem of poor flame retardancy of current TPU materials, the present invention provides a halogen-free flame retardant TPU material and a preparation method thereof, and constructs a hybrid three-dimensional network by combining vinyl-modified aluminum nitride and halloysite nanotubes grafted with furan groups: at the same time, by vinyl-modifying aluminum nitride and grafting furan groups onto halloysite nanotubes, the two can undergo a reversible Diels-Alder reaction to form a thermal conductive network, thereby taking away heat at the initial stage of combustion and prolonging the ignition time. During the combustion process, the multi-level dense and stable carbon layer formed by flexible carboxylated cellulose nanofibers, aluminum nitride and halloysite nanotubes can break the heat conduction path and prevent heat transfer, and reduce the release of smoke and combustible gases, thereby improving the flame retardancy of TPU.
[0004] Technical solution: A halogen-free flame-retardant TPU material, comprising the following components by weight: 100 parts of TPU and 5-10 parts of flame-retardant gas gel particles; The particle size of the fire-resistant gas gel particles is ≤60 μm. Furthermore, the preparation method of the flame retardant gas gel particles is as follows, in parts by weight: Step 1: dissolving 4.5-5 parts of vinyl triethoxysilane in 300 parts of 95% ethanol aqueous solution, stirring at 50°C for 10 minutes, adding 60 parts of aluminum nitride, heating to 80°C, ultrasonically dispersing for 1 hour, washing and drying to obtain vinyl-modified aluminum nitride; Step 2: dissolving 4.5-5 parts of furfural in 300 parts of 95% ethanol aqueous solution, stirring at 50°C for 10 minutes, adjusting the pH value to 3-5 with dilute hydrochloric acid, adding 60 parts of halloysite nanotubes, ultrasonically dispersing for 1 hour, heating to 80°C for reaction for 5-6 hours, centrifuging and washing, and obtaining halloysite nanotubes grafted with furan groups; Step 3: dispersing the vinyl-modified aluminum nitride and the halloysite nanotubes grafted with furan groups in water, and magnetically stirring at 500-600 rpm for 1-2 hours at 60° C. to form a mixed dispersion; Step 4: Mix 20 parts of methoxytrimethylsilane, 1 part of vinyltriethoxysilane and 60 parts of acetic acid solution, stir for 2 hours, and hydrolyze to generate silanol; Step 5: 3-5 parts of the mixed dispersion, 8 parts of silanol and 50 parts of the carboxylated cellulose nanofiber suspension were mixed and stirred at room temperature for 1 hour to form a precursor suspension; Step 6: Place in a mold, freeze with liquid nitrogen, and then freeze-dry to obtain a hybrid aerogel; Step 7: The hybrid aerogel is crushed and heat treated at 80° C. for 2 h to obtain flame-retardant gel particles. Furthermore, the solid content in the mixed dispersion in step 3 is 20 mg / mL. Furthermore, in step 3, the mass ratio of vinyl-modified aluminum nitride to the halloysite nanotubes grafted with furan groups is 1:(1-3). Furthermore, the pH of the acetic acid solution in step 4 is 4. Furthermore, the mass fraction of the carboxylated cellulose nanofiber suspension in step 5 is 0.3%. The preparation method of the above-mentioned halogen-free flame-retardant TPU material comprises the following steps: (1) Take TPU and mix it in a mixer. After the TPU is completely melted, add the flame-retardant gel particles and mix for 10 minutes before taking it out. (2) Adding the mixture to a tablet press for tableting, hot pressing the upper layer for 10 minutes and cold pressing the lower layer for 3 minutes, thereby obtaining a halogen-free flame-retardant TPU material. Furthermore, in step (1), the banburying temperature is 180° C. and the rotation speed is 30 rpm. Furthermore, the hot pressing conditions in step (2) are: the hot pressing temperature is 180° C. and the pressure is 10 MPa. Beneficial effects: 1. The present invention uses flame-retardant gas gel particles as filler, which can effectively improve the flame retardancy of TPU. Aerogel has abundant micro-nano pores, which are helpful for heat dissipation. At the same time, its large specific surface area can also absorb the smoke generated during the thermal decomposition of TPU, thereby improving the smoke suppression effect. 2. The flame-retardant gas gel particles of the present invention use flexible carboxylated cellulose nanofibers as a matrix, halloysite nanotubes as "bricks", and silanol as a "bridge". The bonding network effectively enhances the interfacial bonding, thereby solving the problem of poor mechanical properties of aerogels. 3. The present invention adopts a combination of vinyl-modified aluminum nitride and halloysite nanotubes grafted with furan groups to construct a hybrid three-dimensional network: at the same time, by vinyl-modifying aluminum nitride and grafting furan groups onto halloysite nanotubes, the two can undergo a reversible Diels-Alder reaction to form a thermal conductive network, thereby taking away heat at the initial stage of combustion and prolonging the ignition time. During the combustion process, the multi-level dense and stable carbon layer formed by flexible carboxylated cellulose nanofibers, aluminum nitride and halloysite nanotubes can break the heat conduction path and prevent heat transfer, and reduce the release of smoke and combustible gases, thereby improving the flame retardant properties of TPU. 4. The addition of vinyl-modified aluminum nitride and furan group-grafted halloysite nanotubes in the present invention can prevent the formation of intramolecular hydrogen bonds between flexible carboxylated cellulose nanofibers, thereby increasing the complexity of the aerogel pore structure and improving the flame retardant effect. 5. The Si-O-Si of the silanol in the present invention has endothermic decomposition, dilution and barrier effects, and protective film formation during the combustion process, and can also eliminate anion vacancies on the surface of the aerogel, thereby improving the flame retardant properties. DETAILED DESCRIPTION Example 1 The preparation method of the flame retardant gel particles is as follows, in parts by weight: Step 1: dissolve 5 parts of vinyl triethoxysilane in 300 parts of 95% ethanol aqueous solution, stir at 50°C for 10 minutes, add 60 parts of aluminum nitride, heat to 80°C, ultrasonically disperse for 1 hour, wash and dry to obtain vinyl-modified aluminum nitride; Step 2: dissolving 5 parts of furfural in 300 parts of 95% ethanol aqueous solution, stirring at 50°C for 10 minutes, adjusting the pH value to 4 with dilute hydrochloric acid, adding 60 parts of halloysite nanotubes, ultrasonically dispersing for 1 hour, heating to 80°C for 6 hours, centrifuging and washing, and obtaining halloysite nanotubes grafted with furan groups; Step 3: dispersing vinyl-modified aluminum nitride and halloysite nanotubes grafted with furan groups in water, wherein the mass ratio of vinyl-modified aluminum nitride to the halloysite nanotubes grafted with furan groups is 1:1, and magnetically stirring at 600 rpm for 1.5 h at 60° C. to form a mixed dispersion having a solid content of 20 mg / mL; Step 4: Mix 20 parts of methoxytrimethylsilane, 1 part of vinyltriethoxysilane and 60 parts of acetic acid solution with a pH of 4, stir for 2 hours, and hydrolyze to generate silanol; Step 5: 4 parts of the mixed dispersion, 8 parts of silanol and 50 parts of a 0.3% by mass carboxylated cellulose nanofiber suspension were mixed, and stirred at room temperature for 1 hour to form a precursor suspension; Step 6: Place in a mold, freeze with liquid nitrogen, and then freeze-dry to obtain a hybrid aerogel; Step 7: The hybrid aerogel is crushed and heat treated at 80° C. for 2 h to obtain flame-retardant aerogel particles with a particle size of ≤60 μm. Example 2 The preparation method of the flame retardant gel particles is as follows, in parts by weight: Step 1: dissolve 5 parts of vinyl triethoxysilane in 300 parts of 95% ethanol aqueous solution, stir at 50°C for 10 minutes, add 60 parts of aluminum nitride, heat to 80°C, ultrasonically disperse for 1 hour, wash and dry to obtain vinyl-modified aluminum nitride; Step 2: dissolving 5 parts of furfural in 300 parts of 95% ethanol aqueous solution, stirring at 50°C for 10 minutes, adjusting the pH value to 4 with dilute hydrochloric acid, adding 60 parts of halloysite nanotubes, ultrasonically dispersing for 1 hour, heating to 80°C for 6 hours, centrifuging and washing, and obtaining halloysite nanotubes grafted with furan groups; Step 3: dispersing vinyl-modified aluminum nitride and halloysite nanotubes grafted with furan groups in water, wherein the mass ratio of vinyl-modified aluminum nitride to the halloysite nanotubes grafted with furan groups is 1:2, and magnetically stirring at 600 rpm for 1.5 h at 60° C. to form a mixed dispersion having a solid content of 20 mg / mL; Step 4: Mix 20 parts of methoxytrimethylsilane, 1 part of vinyltriethoxysilane and 60 parts of acetic acid solution with a pH of 4, stir for 2 hours, and hydrolyze to generate silanol; Step 5: 4 parts of the mixed dispersion, 8 parts of silanol and 50 parts of a 0.3% by mass carboxylated cellulose nanofiber suspension were mixed, and stirred at room temperature for 1 hour to form a precursor suspension; Step 6: Place in a mold, freeze with liquid nitrogen, and then freeze-dry to obtain a hybrid aerogel; Step 7: The hybrid aerogel is crushed and heat treated at 80° C. for 2 h to obtain flame-retardant aerogel particles with a particle size of ≤60 μm. Example 3 The preparation method of the flame retardant gel particles is as follows, in parts by weight: Step 1: dissolve 5 parts of vinyl triethoxysilane in 300 parts of 95% ethanol aqueous solution, stir at 50°C for 10 minutes, add 60 parts of aluminum nitride, heat to 80°C, ultrasonically disperse for 1 hour, wash and dry to obtain vinyl-modified aluminum nitride; Step 2: dissolving 5 parts of furfural in 300 parts of 95% ethanol aqueous solution, stirring at 50°C for 10 minutes, adjusting the pH value to 4 with dilute hydrochloric acid, adding 60 parts of halloysite nanotubes, ultrasonically dispersing for 1 hour, heating to 80°C for 6 hours, centrifuging and washing, and obtaining halloysite nanotubes grafted with furan groups; Step 3: dispersing vinyl-modified aluminum nitride and halloysite nanotubes grafted with furan groups in water, wherein the mass ratio of vinyl-modified aluminum nitride to the halloysite nanotubes grafted with furan groups is 1:3, and magnetically stirring at 600 rpm for 1.5 h at 60° C. to form a mixed dispersion having a solid content of 20 mg / mL; Step 4: Mix 20 parts of methoxytrimethylsilane, 1 part of vinyltriethoxysilane and 60 parts of acetic acid solution with a pH of 4, stir for 2 hours, and hydrolyze to generate silanol; Step 5: 4 parts of the mixed dispersion, 8 parts of silanol and 50 parts of a 0.3% by mass carboxylated cellulose nanofiber suspension were mixed, and stirred at room temperature for 1 hour to form a precursor suspension; Step 6: Place in a mold, freeze with liquid nitrogen, and then freeze-dry to obtain a hybrid aerogel; Step 7: The hybrid aerogel is crushed and heat treated at 80° C. for 2 h to obtain flame-retardant aerogel particles with a particle size of ≤60 μm. Example 4 The preparation method of the flame retardant gel particles is as follows, in parts by weight: Step 1: dissolve 5 parts of vinyl triethoxysilane in 300 parts of 95% ethanol aqueous solution, stir at 50°C for 10 minutes, add 60 parts of aluminum nitride, heat to 80°C, ultrasonically disperse for 1 hour, wash and dry to obtain vinyl-modified aluminum nitride; Step 2: dissolving 5 parts of furfural in 300 parts of 95% ethanol aqueous solution, stirring at 50°C for 10 minutes, adjusting the pH value to 4 with dilute hydrochloric acid, adding 60 parts of halloysite nanotubes, ultrasonically dispersing for 1 hour, heating to 80°C for 6 hours, centrifuging and washing, and obtaining halloysite nanotubes grafted with furan groups; Step 3: dispersing vinyl-modified aluminum nitride and halloysite nanotubes grafted with furan groups in water, wherein the mass ratio of vinyl-modified aluminum nitride to the halloysite nanotubes grafted with furan groups is 1:2, and magnetically stirring at 600 rpm for 1.5 h at 60° C. to form a mixed dispersion having a solid content of 20 mg / mL; Step 4: Mix 20 parts of methoxytrimethylsilane, 1 part of vinyltriethoxysilane and 60 parts of acetic acid solution with a pH of 4, stir for 2 hours, and hydrolyze to generate silanol; Step 5: 3 parts of the mixed dispersion, 8 parts of silanol and 50 parts of a 0.3% by mass carboxylated cellulose nanofiber suspension were mixed and stirred at room temperature for 1 hour to form a precursor suspension; Step 6: Place in a mold, freeze with liquid nitrogen, and then freeze-dry to obtain a hybrid aerogel; Step 7: The hybrid aerogel is crushed and heat treated at 80° C. for 2 h to obtain flame-retardant aerogel particles with a particle size of ≤60 μm. Example 5 The preparation method of the flame retardant gel particles is as follows, in parts by weight: Step 1: dissolve 5 parts of vinyl triethoxysilane in 300 parts of 95% ethanol aqueous solution, stir at 50°C for 10 minutes, add 60 parts of aluminum nitride, heat to 80°C, ultrasonically disperse for 1 hour, wash and dry to obtain vinyl-modified aluminum nitride; Step 2: dissolving 5 parts of furfural in 300 parts of 95% ethanol aqueous solution, stirring at 50°C for 10 minutes, adjusting the pH value to 4 with dilute hydrochloric acid, adding 60 parts of halloysite nanotubes, ultrasonically dispersing for 1 hour, heating to 80°C for 6 hours, centrifuging and washing, and obtaining halloysite nanotubes grafted with furan groups; Step 3: dispersing vinyl-modified aluminum nitride and halloysite nanotubes grafted with furan groups in water, wherein the mass ratio of vinyl-modified aluminum nitride to the halloysite nanotubes grafted with furan groups is 1:2, and magnetically stirring at 600 rpm for 1.5 h at 60° C. to form a mixed dispersion having a solid content of 20 mg / mL; Step 4: Mix 20 parts of methoxytrimethylsilane, 1 part of vinyltriethoxysilane and 60 parts of acetic acid solution with a pH of 4, stir for 2 hours, and hydrolyze to generate silanol; Step 5: 5 parts of the mixed dispersion, 8 parts of silanol and 50 parts of a 0.3% by mass carboxylated cellulose nanofiber suspension were mixed, and stirred at room temperature for 1 hour to form a precursor suspension; Step 6: Place in a mold, freeze with liquid nitrogen, and then freeze-dry to obtain a hybrid aerogel; Step 7: The hybrid aerogel is crushed and heat treated at 80° C. for 2 h to obtain flame-retardant aerogel particles with a particle size of ≤60 μm. Comparative Example 1 The difference between this comparative example and Example 2 is that no vinyl-modified aluminum nitride is added, specifically as follows: The preparation method of the flame retardant gel particles is as follows, in parts by weight: Step 1: dissolving 5 parts of furfural in 300 parts of 95% ethanol aqueous solution, stirring at 50°C for 10 minutes, adjusting the pH value to 4 with dilute hydrochloric acid, adding 60 parts of halloysite nanotubes, ultrasonically dispersing for 1 hour, heating to 80°C for 6 hours, centrifuging and washing, and obtaining halloysite nanotubes grafted with furan groups; Step 2: dispersing the furan group-grafted halloysite nanotubes in water, and magnetically stirring at 600 rpm for 1.5 h at 60° C. to form a dispersion with a solid content of 20 mg / mL; Step 3: Mix 20 parts of methoxytrimethylsilane, 1 part of vinyltriethoxysilane and 60 parts of acetic acid solution with a pH of 4, stir for 2 hours, and hydrolyze to generate silanol; Step 4: 4 parts of the dispersion, 8 parts of silanol and 50 parts of a 0.3% by mass carboxylated cellulose nanofiber suspension were mixed and stirred at room temperature for 1 hour to form a precursor suspension; Step 5: Place in a mold, freeze with liquid nitrogen, and then freeze-dry to obtain a hybrid aerogel; Step 6: The hybrid aerogel is crushed and heat treated at 80° C. for 2 h to obtain flame-retardant gas gel particles with a particle size of ≤60 μm. Comparative Example 2 The difference between this comparative example and Example 2 is that the aluminum nitride is not modified, as follows: The preparation method of the flame retardant gel particles is as follows, in parts by weight: Step 1: dissolving 5 parts of furfural in 300 parts of 95% ethanol aqueous solution, stirring at 50°C for 10 minutes, adjusting the pH value to 4 with dilute hydrochloric acid, adding 60 parts of halloysite nanotubes, ultrasonically dispersing for 1 hour, heating to 80°C for 6 hours, centrifuging and washing, and obtaining halloysite nanotubes grafted with furan groups; Step 2: aluminum nitride and halloysite nanotubes grafted with furan groups are dispersed in water, the mass ratio of aluminum nitride to the halloysite nanotubes grafted with furan groups is 1:2, and magnetic stirring is performed at 60° C. and 600 rpm for 1.5 h to form a mixed dispersion with a solid content of 20 mg / mL; Step 3: Mix 20 parts of methoxytrimethylsilane, 1 part of vinyltriethoxysilane and 60 parts of acetic acid solution with a pH of 4, stir for 2 hours, and hydrolyze to generate silanol; Step 4: 4 parts of the mixed dispersion, 8 parts of silanol and 50 parts of a 0.3% by mass carboxylated cellulose nanofiber suspension were mixed, and stirred at room temperature for 1 hour to form a precursor suspension; Step 5: Place in a mold, freeze with liquid nitrogen, and then freeze-dry to obtain a hybrid aerogel; Step 6: The hybrid aerogel is crushed and heat treated at 80° C. for 2 h to obtain flame-retardant gas gel particles with a particle size of ≤60 μm. Comparative Example 3 The difference between this comparative example and Example 2 is that no silanol is added, specifically as follows: The preparation method of the flame retardant gel particles is as follows, in parts by weight: Step 1: dissolve 5 parts of vinyl triethoxysilane in 300 parts of 95% ethanol aqueous solution, stir at 50°C for 10 minutes, add 60 parts of aluminum nitride, heat to 80°C, ultrasonically disperse for 1 hour, wash and dry to obtain vinyl-modified aluminum nitride; Step 2: dissolving 5 parts of furfural in 300 parts of 95% ethanol aqueous solution, stirring at 50°C for 10 minutes, adjusting the pH value to 4 with dilute hydrochloric acid, adding 60 parts of halloysite nanotubes, ultrasonically dispersing for 1 hour, heating to 80°C for 6 hours, centrifuging and washing, and obtaining halloysite nanotubes grafted with furan groups; Step 3: dispersing vinyl-modified aluminum nitride and halloysite nanotubes grafted with furan groups in water, wherein the mass ratio of vinyl-modified aluminum nitride to the halloysite nanotubes grafted with furan groups is 1:2, and magnetically stirring at 600 rpm for 1.5 h at 60° C. to form a mixed dispersion having a solid content of 20 mg / mL; Step 4: 4 parts of the mixed dispersion and 50 parts of a 0.3% by mass carboxylated cellulose nanofiber suspension were mixed, and stirred at room temperature for 1 hour to form a precursor suspension; Step 5: Place in a mold, freeze with liquid nitrogen, and then freeze-dry to obtain a hybrid aerogel; Step 6: The hybrid aerogel is crushed and heat treated at 80° C. for 2 h to obtain flame-retardant gas gel particles with a particle size of ≤60 μm. Comparative Example 4 The difference between this comparative example and Example 2 is that the halloysite nanotubes are not modified, specifically as follows: The preparation method of the flame retardant gel particles is as follows, in parts by weight: Step 1: dissolve 5 parts of vinyl triethoxysilane in 300 parts of 95% ethanol aqueous solution, stir at 50°C for 10 minutes, add 60 parts of aluminum nitride, heat to 80°C, ultrasonically disperse for 1 hour, wash and dry to obtain vinyl-modified aluminum nitride; Step 2: dispersing vinyl-modified aluminum nitride and halloysite nanotubes in water, wherein the mass ratio of vinyl-modified aluminum nitride to the halloysite nanotubes grafted with furan groups is 1:2, and magnetically stirring at 600 rpm for 1.5 h at 60° C. to form a mixed dispersion having a solid content of 20 mg / mL; Step 3: Mix 20 parts of methoxytrimethylsilane, 1 part of vinyltriethoxysilane and 60 parts of acetic acid solution with a pH of 4, stir for 2 hours, and hydrolyze to generate silanol; Step 4: 4 parts of the mixed dispersion, 8 parts of silanol and 50 parts of a 0.3% by mass carboxylated cellulose nanofiber suspension were mixed, and stirred at room temperature for 1 hour to form a precursor suspension; Step 5: Place in a mold, freeze with liquid nitrogen, and then freeze-dry to obtain a hybrid aerogel; Step 6: The hybrid aerogel is crushed and heat treated at 80°C for 2h to obtain flame-retardant gel particles with a particle size of ≤60μm. Various indicators of the aerogel are measured, including physical properties (specific surface area, compression strength) and flame retardancy: Specific surface area: The specific surface area of the sample was measured by a BET automatic adsorption instrument, the temperature was 77K, and the adsorbate was N2; Compression strength: The mechanical properties of the sample were tested using a universal mechanical testing machine, the compression speed was 1mm / min, and the sample was compressed to 70% of the initial diameter and then stopped; the results are shown in Table 1 below: Table 1 After comprehensively comparing the various properties of the above embodiments, the flame-retardant gas gel particles prepared in Embodiment 2 were selected for subsequent tests. Example 6 A method for preparing a halogen-free flame-retardant TPU material comprises the following steps: (1) 100 parts of TPU were mixed in a mixer. After the TPU was completely melted, 5 parts of the flame-retardant gel particles prepared in Example 2 were added. The mixture was mixed for 10 minutes and then taken out. The mixing temperature was 180° C. and the rotation speed was 30 rpm. (2) Adding the mixture to a tablet press for tableting, hot pressing the upper layer for 10 minutes, and cold pressing the lower layer for 3 minutes, to obtain a halogen-free flame-retardant TPU material; wherein the hot pressing temperature is 180° C. and the pressure is 10 MPa. Example 7 A method for preparing a halogen-free flame-retardant TPU material comprises the following steps: (1) 100 parts of TPU were mixed in a mixer. After the TPU was completely melted, 7 parts of the flame-retardant gel particles prepared in Example 2 were added. The mixture was mixed for 10 minutes and then taken out. The mixing temperature was 180° C. and the rotation speed was 30 rpm. (2) Adding the mixture to a tablet press for tableting, hot pressing the upper layer for 10 minutes, and cold pressing the lower layer for 3 minutes, to obtain a halogen-free flame-retardant TPU material; wherein the hot pressing temperature is 180° C. and the pressure is 10 MPa. Example 8 A method for preparing a halogen-free flame-retardant TPU material comprises the following steps: (1) 100 parts of TPU were mixed in a mixer. After the TPU was completely melted, 9 parts of the flame-retardant gel particles prepared in Example 2 were added. The mixture was mixed for 10 minutes and then taken out. The mixing temperature was 180° C. and the rotation speed was 30 rpm. (2) Adding the mixture to a tablet press for tableting, hot pressing the upper layer for 10 minutes, and cold pressing the lower layer for 3 minutes, to obtain a halogen-free flame-retardant TPU material; wherein the hot pressing temperature is 180° C. and the pressure is 10 MPa. Example 9 A method for preparing a halogen-free flame-retardant TPU material comprises the following steps: (1) 100 parts of TPU were mixed in a mixer. After the TPU was completely melted, 10 parts of the flame-retardant gel particles prepared in Example 2 were added. The mixture was mixed for 10 minutes and then taken out. The mixing temperature was 180° C. and the rotation speed was 30 rpm. (2) Adding the mixture to a tablet press for tableting, hot pressing the upper layer for 10 minutes, and cold pressing the lower layer for 3 minutes, to obtain a halogen-free flame-retardant TPU material; wherein the hot pressing temperature is 180° C. and the pressure is 10 MPa. Comparative Example 5 The difference between this embodiment and embodiment 8 is that the flame-retardant gas gel particles prepared in comparative example 1 are used, specifically: A method for preparing a halogen-free flame-retardant TPU material comprises the following steps: (1) 100 parts of TPU were mixed in a mixer. After the TPU was completely melted, 9 parts of the flame-retardant gel particles prepared in Example 2 were added. The mixture was mixed for 10 minutes and then taken out. The mixing temperature was 180° C. and the rotation speed was 30 rpm. (2) Adding the mixture to a tablet press for tableting, hot pressing the upper layer for 10 minutes, and cold pressing the lower layer for 3 minutes, to obtain a halogen-free flame-retardant TPU material; wherein the hot pressing temperature is 180° C. and the pressure is 10 MPa. Comparative Example 6 The difference between this embodiment and embodiment 8 is that the flame-retardant gas gel particles prepared in comparative example 2 are used, specifically: A method for preparing a halogen-free flame-retardant TPU material comprises the following steps: (1) 100 parts of TPU were mixed in a mixer. After the TPU was completely melted, 9 parts of the flame-retardant gel particles prepared in Example 2 were added. The mixture was mixed for 10 minutes and then taken out. The mixing temperature was 180° C. and the rotation speed was 30 rpm. (2) Adding the mixture to a tablet press for tableting, hot pressing the upper layer for 10 minutes, and cold pressing the lower layer for 3 minutes, to obtain a halogen-free flame-retardant TPU material; wherein the hot pressing temperature is 180° C. and the pressure is 10 MPa. Comparative Example 7 The difference between this embodiment and embodiment 8 is that the flame-retardant gas gel particles prepared in comparative example 3 are used, specifically: A method for preparing a halogen-free flame-retardant TPU material comprises the following steps: (1) 100 parts of TPU were mixed in a mixer. After the TPU was completely melted, 9 parts of the flame-retardant gel particles prepared in Example 2 were added. The mixture was mixed for 10 minutes and then taken out. The mixing temperature was 180° C. and the rotation speed was 30 rpm. (2) Adding the mixture to a tablet press for tableting, hot pressing the upper layer for 10 minutes, and cold pressing the lower layer for 3 minutes, to obtain a halogen-free flame-retardant TPU material; wherein the hot pressing temperature is 180° C. and the pressure is 10 MPa. Comparative Example 8 The difference between this embodiment and embodiment 8 is that the flame-retardant gas gel particles prepared in comparative example 4 are used, specifically: A method for preparing a halogen-free flame-retardant TPU material comprises the following steps: (1) 100 parts of TPU were mixed in a mixer. After the TPU was completely melted, 9 parts of the flame-retardant gel particles prepared in Example 2 were added. The mixture was mixed for 10 minutes and then taken out. The mixing temperature was 180° C. and the rotation speed was 30 rpm. (2) Adding the mixture to a tablet press for tableting, hot pressing the upper layer for 10 minutes, and cold pressing the lower layer for 3 minutes, to obtain a halogen-free flame-retardant TPU material; wherein the hot pressing temperature is 180° C. and the pressure is 10 MPa. Determination of the flame retardant properties of the above examples: Flame retardant properties include limiting oxygen index LOI, UL-94 flame retardant rating, peak heat release rate and peak smoke generation rate; The flame retardant and smoke suppression properties of the material were determined using a cone calorimeter. The test standard was ISO 5660 and the thermal radiation power was 50kW / m 2 , sample size is 100×100×3mm 2 , the results are shown in Table 2 below: Table 2
Claims
1. A halogen-free flame-retardant TPU material, characterized in that: The composition comprises the following components in parts by weight: 100 parts of TPU and 5-10 parts of flame-retardant gas gel particles; The particle size of the fire-resistant gas gel particles is ≤60 μm.
2. A halogen-free flame-retardant TPU material according to claim 1, characterized in that: The preparation method of the flame-retardant gas gel particles is as follows, in parts by weight: Step 1: dissolving 4.5-5 parts of vinyl triethoxysilane in 300 parts of 95% ethanol aqueous solution, stirring at 50°C for 10 minutes, adding 60 parts of aluminum nitride, heating to 80°C, ultrasonically dispersing for 1 hour, washing and drying to obtain vinyl-modified aluminum nitride; Step 2: dissolving 4.5-5 parts of furfural in 300 parts of 95% ethanol aqueous solution, stirring at 50°C for 10 minutes, adjusting the pH value to 3-5 with dilute hydrochloric acid, adding 60 parts of halloysite nanotubes, ultrasonically dispersing for 1 hour, heating to 80°C for reaction for 5-6 hours, centrifuging and washing, and obtaining halloysite nanotubes grafted with furan groups; Step 3: dispersing the vinyl-modified aluminum nitride and the halloysite nanotubes grafted with furan groups in water, and magnetically stirring at 500-600 rpm for 1-2 hours at 60° C. to form a mixed dispersion; Step 4: Mix 20 parts of methoxytrimethylsilane, 1 part of vinyltriethoxysilane and 60 parts of acetic acid solution, stir for 2 hours, and hydrolyze to generate silanol; Step 5: 3-5 parts of the mixed dispersion, 8 parts of silanol and 50 parts of the carboxylated cellulose nanofiber suspension were mixed and stirred at room temperature for 1 hour to form a precursor suspension; Step 6: Place in a mold, freeze with liquid nitrogen, and then freeze-dry to obtain a hybrid aerogel; Step 7: The hybrid aerogel is crushed and heat treated at 80° C. for 2 h to obtain flame-retardant gel particles.
3. A halogen-free flame-retardant TPU material according to claim 2, characterized in that: The solid content in the mixed dispersion in step 3 is 20 mg / mL.
4. The halogen-free flame-retardant TPU material according to claim 2, characterized in that: In the step 3, the mass ratio of the vinyl-modified aluminum nitride to the halloysite nanotubes grafted with furan groups is 1:(1-3).
5. The halogen-free flame-retardant TPU material according to claim 2, characterized in that: The pH of the acetic acid solution in step 4 is 4.
6. The halogen-free flame-retardant TPU material according to claim 2, characterized in that: The mass fraction of the carboxylated cellulose nanofiber suspension in step 5 is 0.3%.
7. A method for preparing a halogen-free flame-retardant TPU material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Take TPU and mix it in a mixer. After the TPU is completely melted, add the flame-retardant gel particles and mix for 10 minutes before taking it out. (2) Adding the mixture to a tablet press for tableting, hot pressing the upper layer for 10 minutes and cold pressing the lower layer for 3 minutes, thereby obtaining a halogen-free flame-retardant TPU material.
8. A halogen-free flame-retardant TPU material and a preparation method thereof according to claim 7, characterized in that: In the step (1), the mixing temperature is 180° C. and the rotating speed is 30 rpm.
9. A halogen-free flame-retardant TPU material and a preparation method thereof according to claim 8, characterized in that: The hot pressing conditions in step (2) are: hot pressing temperature is 180° C. and pressure is 10 MPa.
Citation Information
Cited By
Flame-retardant thermal-aging-resistant polyether TPU composite material as well as preparation method and application thereof
CN122483552A